Heat Accumulation, Microstructure Evolution, and Stress Distribution of Ti–Al Alloy Manufactured by Twin‐Wire Plasma Arc Additive. Issue 5 (19th January 2022) - Hou, Xiaoqi; Ye, Xin; Qian, Xiaoyan; Zhang, Xi; Zhang, Peilei; Lu, Qinghua; Yu, Zhishui; Shen, Chen; Wang, Lin; Hua, Xueming
Abstract : Herein, the deposition of a Ti–Al(48 at%) alloy via twin‐wire arc additive manufacturing (WAAM) using plasma arc welding (PAW) and tungsten inert gas (TIG) welding arc sources is presented. The microstructure and the phase composition of different regions of the alloy are analyzed using metalloscopy and X‐ray diffraction. The transient temperature field and residual stress distribution are measured before and after the process, respectively. A transient thermostress model is established using the finite‐element method. Results show that the alloy is composed primarily of α2 ‐Ti3 Al and γ‐TiAl phases, while the microstructure evolution during the Ti–Al(48 at%) alloy deposition process is described. The thermal conductivity in the lower region of the alloy far exceeds that in the middle and upper regions. The thermal conductivity is smaller in the upper region and the midregion, resulting in the increase in heat accumulation. Due to arc shrinkage and reduced heat input, the PAW process reduces the heat accumulation and stress distribution differences more effectively than the TIG process. Abstract : Herein, a comparative study of Ti–Al samples manufactured by twin‐wire arc additive manufacturing (WAAM) using tungsten inert gas (TIG) welding and plasma arc welding (PAW), focusing on heat accumulation, microstructure evolution, and residual stress, is described. The results show that the PAW process achieves a more uniform microstructure and stress distribution.